Pentahelix Implementation Based on “KISS” (Collaboration, Integration, Synchronization, and Synergy) in Local Policy on Flood Management Strategy of the Bodri Kuto River Basin - Yunianto, SR Eko; Sriyana, Ignatius; Suharyanto, Suharyanto (Political Science Program, Universitas Negeri Semarang, 2023)
Collaboration, integration, synchronization, and synergy approaches in water resources management offer more diverse water resources management efforts to deal with flood disaster issues at Bodri Kuto River Basin. The Penta helix-based approach is relevant and essential in the Bodri Kuto River Basin. This study aims to identify stakeholders in the Penta helix elements, determine the impact of the KISS variables in flood management strategies, and determine priority strategies in flood management in the Bodri Kuto River Basin. Pentahelix stakeholders in flood management at Bodri Kuto River Basin consist of parties from the government, private sectors, academics, non-governmental organizations, and the mass media. Based on the results of the KISS index analysis, it is known that the variable synchronization score is included in the